2018
DOI: 10.1007/s11064-018-2542-7
|View full text |Cite
|
Sign up to set email alerts
|

The Peripheral Versus Central Antinociception of a Novel Opioid Agonist: Acute Inflammatory Pain in Rats

Abstract: Opioid analgesics devoid of central side effects are unmet medical need in the treatment of acute pain (e.g. post-operative pain). Recently, we have reported on 14-O-methylmorphine-6-O-sulfate (14-O-MeM6SU), a novel opioid agonist of high efficacy producing peripheral antinociception in subchronic inflammatory pain in certain doses. The present study focused on the antinociceptive effect of 14-O-MeM6SU compared to morphine in formalin test of an early/acute (Phase I) and late/tonic (Phase II) pain phases. Subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…On the other hand, this automat-ed technique can be he formalin test, especially considered for the detection of analgesic drugs. From a general point of view, the NSAIDs used are in agreement with previous studies showing that opioids with restricted penetration into the CNS can reduce somatic and inflammatory pain by acting at the peripheral level [13][14][15].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, this automat-ed technique can be he formalin test, especially considered for the detection of analgesic drugs. From a general point of view, the NSAIDs used are in agreement with previous studies showing that opioids with restricted penetration into the CNS can reduce somatic and inflammatory pain by acting at the peripheral level [13][14][15].…”
Section: Discussionsupporting
confidence: 87%
“…At the present, we speculate that in the rat tail-flick test, which is an acute thermal pain model and MORs are not undertaken to substantial changes related to their number, the peripheral MOR reserve is not large enough for C6SU to produce stronger analgesic effect. Therefore, based on the above, we further extended our studies to examine the effect of 14-OMeC6SU compared to C6SU in animal pain model whereas the MORs reserve is significantly up-regulated [7,42,43]. Thus, CFA-induced inflammatory pain model suits the prerequisite condition for partial agonists-like C6SU in the present work-because ours and other research groups have reported on increased peripheral MOR expression in the inflamed paw in this model [37].…”
Section: Discussionmentioning
confidence: 68%
“…In addition, pharmacological evidence has shown that opioids are also capable to produce antinociception by the activation of opioid receptors reside outside the central nervous system [4][5][6][7][8][9][10]. Indeed, opioid agonists that have been reported to induce peripheral antinociception display a prerequisite physiochemical property, a limited central nervous system (CNS) penetration [4,5,7]. Thus, over the last four decades many opioid research groups have undertaken the task of synthesis and pharmacological characterization of opioid compounds with limited CNS penetration and thereby inducing antinociception by activating opioid receptors at the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…The restricted capability to enter the CNS of compounds 2 – 5 was earlier demonstrated experimentally employing a commonly used pharmacological approach. 35,39,60,61 Antinociceptive effects of 2 – 5 in pain models of thermal nociception (tail-flick test) 45 and inflammatory hyperalgesia in the rat (the formalin test and carrageenan-induced hyperalgesia) 46,49 after systemic sc administration were completely blocked by sc naloxone methiodide, an opioid antagonist that does not cross the BBB. 27 Furthermore, naloxone methiodide completely antagonized antinociceptive effects of 6β-Gly-substituted 2b in the mouse eye wiping behavioral test for trigeminal nociception following systemic ip administration.…”
Section: Resultsmentioning
confidence: 99%